Role of uncoupling protein 2 in right heart hypertrophy - Esfandiary, Azadeh; Justus Liebig University Giessen (My University, 2018)
RVF occurs when mechanisms compensating an increased RV afterload e.g. caused by PH, pulmonary vascular stenosis, etc. are exhausted. We hypothesized that transition from compensation to decompensation of the RV may be promoted by changes in cardiomyocytes calcium dynamics, release of ROS and metabolism. Therefore, we investigated the role of mitochondrial uncoupling protein 2 (UCP2) in a murine model of RV hypertrophy and failure. Pressure overload was induced by PAB in UCP2 deficient mice (UCP2-/-) and in C57BL/6J mice. Three weeks after PAB or sham operation, right heart hypertrophy and function were determined by invasive hemodynamics and echocardiography. Contraction and relaxation of cardiomyocytes isolated from these mice, as well as cellular calcium dynamics and mitochondrial superoxide release were measured by fluorescence microscopy. Expression of the cardiac calcium handling proteins SERCA2a, PLB and the NCX, as well as MFN2, which is a mitochondrial protein that has been shown to influence mitochondrial-SR interaction, were determined by immunoblotting. Mitochondrial superoxide release and respiration were determined by the fluorescent dye MitoSOX, and high resolution respirometry, respectively. Echocardiographic and hemodynamic assessments revealed that: PAB induced increased right ventricular systolic pressure (RVSP) and right heart hypertrophy in C57BL/6J and UCP2-/- mice PAB induced a decrease of CO and RV dilation as signs of RV decompensation in C57BL/6J mice Right ventricular function was preserved after PAB in UCP2-/- mice in contrast to C57BL/6J mice Functional studies in cardiomyocytes revealed that: Cardiomyocytes isolated from the RV of both, C57BL/6J and UCP2-/- mice, showed increased contractility, despite decrease of CO in C57BL/6J mice Cardiomyocytes isolated from the RV of UCP2-/- mice showed further improved function after PAB compared to C57BL/6J mice Cardiomyocytes isolated from the RV of UCP2-/- mice showed improved contraction and relaxation after PAB compared to C57BL/6J mice Analysis of calcium dynamics in isolated cardiomyocytes revealed that: Calcium transients were increased in cardiomyocytes from UCP2-/- mice after PAB compared to C57BL/6J mice The time of calcium to reach 50% of the basal value was decreased in cardiomyocytes from UCP2-/- mice after PAB compared to C57BL/6J mice Expression of calcium handling proteins in cardiomyocytes revealed that: SERCA2a expression was increased in RV cardiomyocytes from UCP2-/- mice after PAB compared to C57BL/6J mice MFN2 expression was increased in RV cardiomyocytes from UCP2-/- mice after PAB compared to C57BL/6J mice NCX expression and PLB expression were unchanged in cardiomyocytes from UCP2-/- mice after PAB compared to C57BL/6J mice ROS studies in cardiomyocytes and mitochondrial respiration in muscle fibers revealed that: Isolated cardiomyocytes from UCP2-/- mice after PAB showed increased mitochondrial superoxide concentration under stimulation compared to C57BL/6J mice ROS inhibition by superoxide scavenger tempol decreased cardiomyocyte function and contractility Mitochondrial respiration in permeabilized muscle fibers remained unchanged independent of genotype and treatment We conclude that UCP2 deficiency may protect from pressure overload-induced RV dysfunction via improved cardiomyocyte calcium dynamics due to increased SERCA2a expression. Regulation of calcium dynamics due to increased SERCA2a may be regulated by increased ROS release. Therefore, UCP2 deletion and SERCA2a may be considered as novel therapeutic targets to inhibit transition from compensated RV hypertrophy to RVF.

Zu einem Versagen des rechten Ventrikels (RV) kommt es, wenn das rechte Herz nicht länger in der Lage ist eine gesteigerte RV Nachlast, wie sie z.B. durch eine pulmonale Hypertonie oder eine pulmonal-vaskuläre Stenose verursacht wird, zu kompensieren. Das Ziel dieser Arbeit war es, zu überprüfen, welche Mechanismen für den Übergang von einer kompensierten zu einer dekompensierten Rechtsherzfunktion verantwortlich sind. Die zugrundeliegende Hypothese war, dass Änderungen in der Kalziumdynamik von Kardiomyozyten oder/und die Freisetzung reaktiver Sauerstoffspezies (ROS) und des zellulären Metabolismus verantwortlich für die Dekompensation des Herzens sind. Aufgrund seiner Beteiligung an den oben genannten Mechanismen sollte die Rolle des mitochondrialen entkoppelnden Proteins 2 (mitochondrial uncoupling protein 2, UCP2) beim Rechtsherzversagen in einem Mausmodell des pulmonalarteriellen bandings (PAB) untersucht werden. Zur Erzeugung eines erhöhter RV Druckes wurden sowohl UCP2-defiziente (UCP2-/-) als auch WT (C57BL/6J) Mäuse einer PAB- oder Sham- (gleicher Eingriff ohne Ligatur der Pulmonalarterie) Operation unterzogen. Drei Wochen nach der jeweiligen Operation wurde mittels hämodynamischer Messungen und Echokardiographie der Grad der Hypertrophie und die Funktion des RV untersucht. Weiterhin wurde unter Zuhilfenahme von Fluoreszenzmikroskopie die Kontraktion und Relaxation isolierter Kardiomyozyten sowie die zelluläre Kalzium-Dynamik und die mitochondriale Superoxid-Freisetzung gemessen. Zusätzlich wurde die Expression von Proteinen, die am Kalziumtransport der Kardiomyozyten beteiligt sind, der sarco endoplasmatic reticulum calcium ATPase 2a (SERCA2a), Phospholamban (PLB) und des sarkolemmalen Natrium-Kalzium-Austauschers (NCX), sowie von Mitofusin-2 (MFN2), dass auch die Interaktion von Mitochondrien und SR reguliert, in Kardiomyozyten anhand von Immunoblots quantifiziert. Schließlich wurde noch die Respiration mittels hochauflösende Respirometrie bestimmt. Die echokardiographischen und hämodynamischen Untersuchungen zeigten, dass PAB bei C57BL/6J- und UCP2-/--Mäusen zu einer vergleichbaren Erhöhung des rechtsventrikulären systolischen Druck führte, PAB eine rechtsventrikuläre Hypertrophie bei C57BL/6J- und UCP2-/--Mäusen induzierte, PAB eine Abnahme des CO und RV Dilatation, als Zeichen der RV Dekompensation in C57BL/6J mice induzierte und die rechtsventrikuläre Funktion bei UCP2-/--Mäusen im Gegensatz zu den WT Mäusen erhalten blieb. Die funktionalen Studien an Kardiomyozyten verdeutlichten, dass die Kontraktilität von isolierten Kardiomyozyten sowohl von C57BL/6J, als auch UCP2-/- Mäusen erhöht war, trotz einer Abnahme des CO in C57BL/6J Mäusen, die Funktion, Kontraktion und Relaxation der isolierten RV Kardiomyozyten von UCP2-/--Mäusen nach PAB besser war als die der Kardiomyozyten von C57BL/6J-Mäusen. Die Analyse der Kalzium-Dynamik in isolierten Kardiomyozyten wiesen daraufhin, dass die Kalziumströme der Kardiomyozyten von UCP2-/--Mäusen nach PAB gesteigert waren verglichen mit denen von C57BL/6J-Mäusen, bei UCP2-/--Mäusen die Halbwertszeit bis zum Erreichen von 50% des Kalzium-Grundwertes kürzer war als die der C57BL/6J-Mäuse. Die Expression der Kalzium-transportierenden Proteine in den Kardiomyozyten zeigte, dass nach PAB die Expression von SERCA2a, MFN2 und PLB in den RV Kardiomyozyten der UCP2-/--Mäuse erhöht war verglichen mit der Expression der C57BL/6J-Mäusen, die Expression von NCX in den Kardiomyozyten der UCP2-/-- und C57BL/6J-Mäusen nach PAB nicht unterscheidbar war. Die Untersuchungen zur ROS-Freisetzung in Kardiomyozyten und zur mitochondrialen Respiration in Muskelfasern ergaben, dass isolierte Kardiomyozyten der UCP2-/--Mäuse nach PAB bei Stimulation eine erhöhte mitochondriale Superoxid-Konzentration aufwiesen als die der C57BL/6J-Mäuse, eine ROS-Inhibition durch den Superoxid-Fänger Tempol die Funktion und Kontraktilität der Kardiomyozyten beeinträchtigte, sich die mitochondriale Respiration permeabilisierter Muskelfasern unabhängig von Genotyp und Behandlung nicht veränderte. Die Ergebnisse dieser Arbeit zeigen, dass eine Deletion des UCP2-vor einer RV Dysfunktion hervorgerufen durch eine erhöhte Nachlast schützt, indem es aufgrund einer gesteigerten SERCA2a-Expression zu einer verbesserten Kalzium-Dynamik der Kardiomyozyten führt. Diese Regulierung der Kalzium-Dynamik wird vermutlich durch eine erhöhte ROS-Freisetzung hervorgerufen. Aus diesen Gründen handelt es sich bei SERCA2a und UCP2 um potentielle neue Ziele für die Therapie der maladativen Rechtsherzhypertrophie.
Die Rolle des entkoppelnden Protein 2 in Rechtsherzhypertrophie
Keywords: Uncoupling protein; right heart hypertrophy; mitochondria; ddc:610